Komparasi Keaktifan dan Hasil Belajar Matematika Siswa pada Penerapan Model Pembelajaran TAI dan TGT - Nur Qalbi Tayibu (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
This study aims to determine: (1) students' mathematics learning outcomes before and after the application of TAI learning model, (2) students' mathematics learning outcomes before and after the application of TGT learning model, (3) students' learning activeness during the application of TAI and TGT learning models, (4) there is a significant difference between the improvement of students' mathematics learning outcomes in the application of TAI and TGT learning models. The population of this study were all students of class X SMK YAPIKA Makassar with the research sample, namely class X¬4 as many as 29 people and 32 people from class X3. Research conclusions: (1) The mathematics learning outcomes of X4 class students before and after the application of the TAI learning model, the average scores were 53.21 and 75.07. (2) The mathematics learning outcomes of X3 class students before and after the application of the TGT learning model, the average scores were 56.30 and 77.12 (3) The learning activeness of X4 class students during the application of the TAI and TGT learning models, the average scores were 30.25 and 28.5 (high category). Hypothesis testing obtained a significant value> 0.05 = 0.274 then H0 is accepted.